Studi Tentang Partisipasi Perempuan dalam Pengambilan Keputusan Musyawarah Leo di Kabupaten Rote Ndao - Tulle, Kiki Else Dorline (Paradigma: Jurnal Kajian Budaya, 2016)
Women participation in decision making is a manifestation of equality between men and women. Public arena is dominated by men meanwhile the women were put mainly only on domestic domain and almost didn’t have any access to the public arena. Main issue of this research was the women participation in decision making in Leo discussion at Rote Ndao district. This was a descriptive qualitative research with phenomenological and cultural approaches. Data collection techniques used were interview with informants, observation and document analysis. From this research it was known that the women participation in Leo discussion was limited only on giving comments and advices, final decision was then made by the male, because tradition said that men had the rights on decision making. Although still dominated by men, there were some women participation in Leo discussion, women could made decision which related to technical means issues in Leo discussion. Public area were still dominated by men and its domestic counterparts were still fully done by the womens. Women were heard if they were highly educated, women were respected when they were experienced, oldest, had life character which put in high regard, not arrogant, motherly, mildly resolute, and used to public appearances.